Radio and print - different strengths - Chinyamunyamu, Betty (Technical Centre for Agricultural and Rural Cooperation, 2005)
Betty Chinyamunyamu, Director of NASCENT, the development wing of the National Smallholders Association of Malawi explains the different advantages of print and radio to provide information to farmers.